Constitutional conventions in South Africa : a reappraisal - Leyshon, Donald John (Department of Public Law, 2021)
This work deals with aspects of constitutional development in South Africa from Union in 1910 until 1983. More specifically, it examines the important role played by constitutional conventions in this country, drawing extensively upon local, British and other Commonwealth materials for this purpose. Reference to British and other Commonwealth experience of conventions is justified, because South Africa enjoys a constitutional heritage richly endowed from the United Kingdom2 and from the other former Dominions of the British Crown. The common bond between South Africa and many of these countries is a system of government often referred to as the 'Westminster System. A brief description of this common constitutional heritage or 'Westminster System' is required before a proper analysis of constitutional conventions can be undertaken.